Aids and accusation : Haiti and the geography of blame - Farmer, Paul, 1959-2022 (Comparative studies of health systems and medical care., 2006)
In this dissertation, ethnographic, historical and epidemiologic data are brought to bear on the subject of the Acquired Immune Deficiency Syndrome (AIDS) in Haiti. The forces that have helped to determine rates and pattern of spread of Human Immunodeficiency Virus (HIV) are examined, as are social responses to AIDS in rural and urban Haiti, and in parts of North America. History and its calculus of economic and symbolic power also help to explain why residents of a small village in rural Haiti came to understand AIDS in the manner that they did. Drawing on several years of fieldwork, the evolution of a cultural model of AIDS is traced. In a small village in rural Haiti, it was possible to document first the lack of such a model, and then the elaboration over time of a widely shared representation of AIDS. The experience of three villagers who died of complications of AIDS is examined in detail, and the importance of their suffering to the evolution of a cultural model is demonstrated. Epidemiologic and ethnographic studies are prefaced by a geographically broad historical analysis, which suggests the outlines of relations between a powerful center (the United States) and a peripheral client state (Haiti). These relations constitute an important part of a political-economic network termed the "West Atlantic system." The epidemiology of HIV and AIDS in Haiti and elsewhere in the Caribbean is reviewed, and the relation between the degree of involvement in the West Atlantic system and the prevalence of HIV is suggested. It is further suggested that the history of HIV in the Dominican Republic, Jamaica, Trinidad and Tobago, and the Bahamas is similar to that documented here for Haiti